Cumulating the intellectual gold of case study - Jensen, Jason L.; Rodgers, Robert (2001)
Two criticisms of public administration research have been leveled. First, knowledge in the field is not being cumulated. Second, the research has low quality. A preference for case studies as a form of scientific inquiry is behind both criticisms. The authors propose a solution to the first problem by showing how meta-analysis can be used to cumulate knowledge using case study evidence. Viewed cumulatively, case studies comprise on intellectual goldmine awaiting discovery. The authors challenge the second criticism, proposing that quality judgments should be based on the important principle of knowledge cumulation, which acknowledges the value of all research methods. - Reproduced
Keywords: Research; Public administration